Variation in physicochemical properties of seed of selected improved varieties of cowpea as it relates to industrial utilization of the crop - Ajeigbe, Hakeem A.; Ihedioha, D.; Chikoye, David (2008)
Cowpea is an important food, cash and fodder crop in Sub-Saharan Africa and has potential of becoming an industrial crop. A trial was conducted to evaluate selected improved and popular varieties of cowpea for physicochemical characteristics that can help to promote commercial production and industrial use. Variations in content were found among varieties for protein (21.3 - 26.9%), carbohydrate (63.37 - 69.56%), fat (1.2 to 1.80%), crude fibre (0.43 to 1.03%), and tannin (0.87 - 1.51 mg/g), also in water binding capacity (91.77 - 108.35%) and gelatinization temperature (79.13 - 84.83oC). High positive correlations (0.86) were observed between the content of fat and crude fibre, ash and protein (0.78), carbohydrate and viscosity of cowpea flour (0.76), and between ash and tannin (0.61) content of cowpea seed, negative correlations were observed between the content of crude protein and carbohydrate (- 0.98), ash and fat (-0.78), crude protein and viscosity (-0.76) of cowpea flour, fat and water binding capacity of cowpea flour (-0.72) and carbohydrate and tannin (-0.54) in cowpea seed. Seed coat colour plays no significant role in the chemical content of the seed. The physicochemical properties evaluated generally had high broad sense heritability (56 - 99%). Cowpea varieties (IT97K-1101-5 and IT89KD-288) with high protein content could be selected for formulating infant feeds, varieties with lower carbohydrate, low fat and high crude fibre (IT90K-277-2) would be desirable in making meals for diabetic patients.